Identifying Reading Delays Among Early-Grade Students in Civics Learning: Evidence from a Descriptive Qualitative Study in Indonesia - Ika Maya Evilia; Kristi Wardani; Wachid Pratomo (Journal of Innovation and Research in Primary Education, 2026)
Reading delay in subject-specific instructional contexts remains an underexplored phenomenon in early literacy research, particularly within Civics learning. This study aimed to analyze the causal factors underlying reading delays among second-grade elementary school students and to identify effective teacher strategies to address them. A descriptive qualitative design was employed, with three purposively selected second-grade students at Al Madina Elementary School, Purworejo, Indonesia, serving as research subjects. Data were collected through structured observation, structured interviews, and documentation over two months and analyzed using Miles et al.'s inductive thematic analysis framework. The findings reveal a dual-factor structure: all three subjects exhibited letter-recognition deficits, while differing in primary causal pathways—intellectual (slow learner profile) or environmental (absent parental support, low motivation). Two unexpected findings emerged: one subject's motivational withdrawal proved relationally contingent rather than dispositionally fixed, and another expressed social shame about reading inability—an affective barrier not previously documented in Civics-specific research. The teacher implemented a four-week scaffolded intervention progressing from phonological drills to manipulative letter-card tasks, which increased on-task engagement across all subjects. This study contributes subject-specific qualitative evidence of reading delay within Civics instruction and highlights curriculum textbook design as a structural barrier warranting further scholarly attention.